Ursolic Acid Induces Multifaceted Defense Responses Against Postharvest Blue Mold Rot in Apple Fruit - Chang Shu; Wenxiao Jiao; Kuanbo Cui; Jiankang Cao; Weibo Jiang (Foods)
The disease resistance and defense mechanisms induced by ursolic acid (UA) in apple fruit were studied in this paper. UA was directly mixed with potato dextrose agar and broth media to assay its antifungal activity in vitro. The results showed that UA exerted inherent antifungal activity and directly inhibited the in vitro growth and spore germination of Penicillium expansum. Its half-maximal inhibitory concentration for hyphal growth was 175.6 mg L−1. Apple fruit were immersed in UA solution, followed by inoculation with P. expansum, to measure their disease response. The results demonstrated that UA induced significant disease resistance in apple fruit and that its mechanisms are multifaceted and associated with defensive and antioxidative enzymes and the phenylpropanoid pathway. Chitinase, β-1,3-glucanase, peroxidase, and polyphenol oxidase were activated and maintained at relatively high levels. The activities of enzymes and their metabolites in the phenylpropanoid pathway, including phenylalanine ammonia-lyase, cinnamate-4-hydroxylase, and 4-coumarate coenzyme A ligase were significantly increased; accordingly, total phenolics, flavonoid, and lignin contents were significantly increased. The activities of superoxide dismutase, ascorbate peroxidase, and glutathione reductase were enhanced upon UA treatment, while catalase activity was suppressed, which regulates hydrogen peroxide accumulation to defend against pathogens. These results suggest that UA induces defense responses against postharvest blue mold rot in apple fruit and that it may be a promising elicitor to induce fruit disease resistance to control postharvest decay.